PENGARUH DIFERENSIASI PRODUK â€œGREEN TOURISM DESTINATIONâ€ TERHADAP KEPUASAN BERKUNJUNG DI PULAU SIKUAI (Survey terhadap pengunjung di Pulau Sikuai Sumatera Barat) - Permana, Dian; Purnama, Ridwan (THE Journal : Tourism and Hospitality Essentials Journal, 2013)
The development and growth of maritime tourism in Indonesia nowadays become a prominence that can be created as a maritime destination in world level. Indonesiaâ€™s Sabang until Merauke store millions of the beauty of natures that are unique and can not be found in other place even there are not many people know it. One of many potentials that Indonesia has, there is Pulau Sikuai which is located in Pantai Padang, West Sumatera. Pulau Sikuai in its development does really keep and concern about the natural of environment, and also support the â€œgreenâ€ concept that is being conducted by the local government and central government. So as it becomes own differentiation of Pulau Sikuai in giving the product and more satisfaction to the visitors because of taking part in preserving nature and environment. The product differentiation of Pulau Sikuai â€œgreen tourism destinationâ€ consists of features, performance, style and design. Based on the explanation, the research is done to know about the visiting satisfaction that is viewed from product differentiation â€œgreen tourism destinationâ€. Analysis unit of the research is the visitors with the population reaches until 80 persons. The method that is done in this research is descriptive method and verification method, the research is conducted in less than one year period of time, so that it is used cross sectional method. The data that is used is primary data and secondary data which is conducted through literature study and questionnaire. To measure how big the impact of product differentiation â€œgreen tourism destinationâ€ to the visiting satisfaction in Pulau Sikuai, the multiple regression is performed. Based on the hypothesis statistic, product differentiation â€œgreen tourism destinationâ€ which consists of features, performance, style and design can influence the visiting satisfaction in Pulau Sikuai. Where the variable features mempengaruih visit satisfaction of 34.82%, while affecting the performance of 17.52% visit satisfaction, style and design affect the satisfaction of visiting at 3.06%.